Child Welfare Outcomes During the 1990s : Voume 1. Executive Summary - World Bank (Washington, DC, 2013)
The objective of this study is to 1) review the situation and trends in terms of child welfare outcomes in Russia; 2) review and evaluate social policy responses; 3) identify major issues and challenges; and 4) propose policies and measures that would improve child well-being outcomes. The study consists of two parts. the first part reviews child welfare outcomes during the 1990s, focusing on child poverty and vulnerability, as well as health, education, and nutrition status. Chapter 2 links child well-being outcomes to the protracted economic crisis and related labor market developments, high inequality, rapid demographic and family formation changes, as well as generally insufficient, severely fiscally constrained and ineffective policy responses. Chapter 3 examines public policy responses in social protection, health and education, focusing on safety nets particularly policies targeting families and children. the second part of the study focuses on two groups of children identified as particularly vulnerable in Russia: children deprived of birth family upbringing and children with disabilities. the chapter on the former highlights their growing numbers against a continued decline in the child population, as well as the continued practice of costly, detrimental to child development and ineffective long-term institutionalization of such children. It reviews legal and institutional reforms undertaken so far and identifies challenges related to designing effective reform.